Does it pay to be ethical? Evidence from the FTSE4Good - Belghitar, Yacine; Clark, Ephraim; Deshmukh, Nitin (Elsevier, 2014)
The empirical mean–variance evidence comparing the performance of Socially Responsible Investments (SRI) and conventional investments suggests that there is no significant difference between the two. This paper re-examines the problem in the context of Marginal Conditional Stochastic Dominance (MCSD), which can accommodate any return distribution or concave utility function. Our results provide strong evidence that there is a financial price to be paid for socially responsible investing. Indices composed of socially responsible firms are MCSD dominated by trademarked indices composed of conventional firms as well as by indices carefully matched by size and industry with the firms in the SRI indices. Zero cost portfolios created by shorting the SRI index and using the proceeds to invest in the conventional index generate higher average returns, lower variance and higher skewness than either of the two indices standing alone. They also MCSD dominate the SRI and conventional indices standing alone.
Keywords: Socially Responsible Investments; SRI; Marginal Conditional Stochastic Dominance